Marked dissociation of photopic and mesopic contrast sensitivity even in normal observers - Hertenstein, Hannah Magdalena; Bach, Michael; Gross, Nikolai Johannes; Beisse, Flemming (Graefe's archive for clinical and experimental ophthalmology, 2016)
Although contrast vision is not routinely tested, it is important: for instance, it predicts traffic incidents better than visual acuity. Mesopic contrast sensitivity (CS) testing approximates low-lighting conditions but entails dark adaptation, which can disrupt clinical routine. In receptor-specific diseases, a dissociation of photopic and mesopic sensitivity would be expected, but can photopic CS act as a surrogate measure for mesopic CS, at least for screening purposes?